Variabilidade morfodinâmica das praias oceânicas entre Imbé e Arroio do Sal, RS, Brasil - Weschenfelder, Jair (2002)
The morphodynamic variability of the oceanic beaches between Imbé and Arroio do Sal towns, Rio Grande do Sul State, Brazil, was investigated by means of periodic beach profiling combined with the interpretation of granulometric and hydrodynamic regime data. A seasonal trend in the hydrodynamic regime, in the distribution of the sediments and in the morphometric and morphodynamic parameters analyzed, was identified. Seasonality is marked by the dominance of accretionary profiles during the summer and erosional profiles during the winter. These beaches were classified according to their morphodynamic state, as dissipative and intermediate.